Fatty acid amide hydrolase inhibitors: a patent review (2009 – 2014). (2nd November 2015) - Lodola, Alessio; Castelli, Riccardo; Mor, Marco; Rivara, Silvia
Abstract : Introduction: Fatty acid amide hydrolase (FAAH) is a key enzyme responsible for the degradation of the endocannabinoid anandamide. FAAH inactivation is emerging as a strategy to treat several CNS and peripheral diseases, including inflammation and pain. The search for effective FAAH inhibitors has thus become a key focus in present drug discovery. Areas covered: Patents and patent applications published from 2009 to 2014 in which novel chemical classes are claimed to inhibit FAAH. Expert opinion: FAAH is a promising target for treating many disease conditions including pain, inflammation and mood disorders. In the last few years, remarkable efforts have been made to develop new FAAH inhibitors (either reversible and irreversible) characterized by excellent potency and selectivity, to complete the arsenal of tools for modulating FAAH activity. The failure of PF-04457845 in a Phase II study on osteoarthritis pain has not flattened the interest in FAAH inhibitors. New clinical trials on 'classical' FAAH inhibitors are now ongoing, and new strategies based on compounds with peculiar in vivo distribution (e.g., peripheral) or with multiple pharmacological activities (e.g., FAAH and COX) are under investigation and could boost the therapeutic potential of this class in the next future.